If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5y + 1)(5 + y) = 0 Reorder the terms: (1 + 5y)(5 + y) = 0 Multiply (1 + 5y) * (5 + y) (1(5 + y) + 5y * (5 + y)) = 0 ((5 * 1 + y * 1) + 5y * (5 + y)) = 0 ((5 + 1y) + 5y * (5 + y)) = 0 (5 + 1y + (5 * 5y + y * 5y)) = 0 (5 + 1y + (25y + 5y2)) = 0 Combine like terms: 1y + 25y = 26y (5 + 26y + 5y2) = 0 Solving 5 + 26y + 5y2 = 0 Solving for variable 'y'. Factor a trinomial. (5 + y)(1 + 5y) = 0Subproblem 1
Set the factor '(5 + y)' equal to zero and attempt to solve: Simplifying 5 + y = 0 Solving 5 + y = 0 Move all terms containing y to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + y = 0 + -5 Combine like terms: 5 + -5 = 0 0 + y = 0 + -5 y = 0 + -5 Combine like terms: 0 + -5 = -5 y = -5 Simplifying y = -5Subproblem 2
Set the factor '(1 + 5y)' equal to zero and attempt to solve: Simplifying 1 + 5y = 0 Solving 1 + 5y = 0 Move all terms containing y to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 5y = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 5y = 0 + -1 5y = 0 + -1 Combine like terms: 0 + -1 = -1 5y = -1 Divide each side by '5'. y = -0.2 Simplifying y = -0.2Solution
y = {-5, -0.2}
| 5x^3+2x^2=20x+8 | | 3.2s-5=5-18 | | 3x+u=7 | | 3a-16=31 | | 5(1-x)=-5(6x-6) | | 223=6*x+7 | | 12.6=x*40 | | 9(-10+x)-5(2x+9)=4-x+11 | | 5x-50=15 | | -19y=2x+.05 | | 6x+2+2-3x=-4(6x-3)+3(-x-3) | | 6a+17=-1 | | -2(2x+5)=-2+4x | | .27=x*75 | | x+.07x=15877 | | (4x+8y^2)(x-y^2)=0 | | 5h+21=11 | | W-19=6+9w | | 4(-4x+6)=-6(1+2x)-x | | X+x*4-144=0 | | -p+5=25-6p | | -5(k-3)=-90 | | 3g+17=5 | | .75*80= | | 2-x=-5(x-2) | | 4f-3=13 | | -3+2x=-(4-x) | | 2sin(x)-3=-2 | | 5d-7=23 | | 7=2x^2+6x+7 | | -3(5+3x)=4x-2 | | B+8=1 |